Aplikasi Enterprise Resource Planning Bagian Modul Penjualan di Lima Perusahaan Distributor dan Dealer - Raymond Wijaya; Adi Wibowo; Rudy Adipranata (Jurnal Infra, 2016)
At this time there is no ERP applications specifically tailored to the needs of distribution companies. System in ERP applications that exist today only answers the needs of the company in general. It is important to address the needs of the company's sales distribution module. Distribution companies studied are distributors of crops, fruit distributor, motorcycle dealers, distributors of electronic goods and components distributor panel. From the background of these problems, designed a structured sales module for five companies distributors and dealers. The application is made by using the CodeIgniter PHP programming language and MySQL for the database. Results obtained from these applications include the recording of the master, sales transactions, transaction settlement of debt, transaction delivery, transaction sales returns, reports sales returns, sales reports, report card stock, the report claims, the report card receivables and income statement for five company. This thesis can accommodate the process of selling five companies distributors and dealers who have been determined.